Evaluating an Intervention to Reduce Risky Driving Behaviors: Taking the Fear Out of Virtual Reality. Issue 9 (20th November 2020) - Cutello, Clara Alida; Gummerum, Michaela; Hanoch, Yaniv; Hellier, Elizabeth
Abstract: Educational programs are the most common type of intervention to reduce risky driving behavior. Their success, however, depends on the content of the material used and the mode of delivery. In the present study, we examined the impact of fear versus positively framed road safety films and traditional technologies (2D) versus emerging technologies (VR) on young drivers' self‐reported risky driving behaviors. One hundred and forty‐six university students completed a similar set of questionnaires pre‐intervention and post‐intervention, two weeks later. In addition, they were randomly assigned to one of the four experimental conditions (VR vs. 2D; positive vs. negative). In the VR conditions, the film was presented using an HTC VIVE Virtual Reality headset. In the 2D conditions, the film was presented on a computer screen. Measures evaluating attitudes toward risky driving behavior were completed at both time frames, questions regarding the participants' emotional arousal were asked at pre‐intervention as a manipulation check, and questions regarding willingness to take risks in potentially dangerous driving situations were asked at follow‐up. The findings indicate that the positively framed films significantly decreased self‐reported risky driving behaviors in both modalities, but especially when viewed in VR format. In contrast, the fear appeal film, when shown in VR, failed to reduce risky driving behaviors, and in fact, increased young drivers' self‐reported risky driving behaviors. Theoretical frameworks regarding the strengths and weaknesses of fear appeals and positively framed appeals are discussed to aid future research to reduce risky driving. Practical implications on the future usage of VR are also considered.